Acute Kidney Injury Associated With Red Yeast Rice (Beni-kōji) Supplement: A Report of Two Cases - Kiyotaka Uchiyama; Masako Otani; Naoki Chigusa; Kazuya Sugita; Ryosuke Matsuoka; Koji Hosoya; Mina Komuta; Jun Ito; Naoki Washida (Kidney Medicine)
Numerous health concerns, primarily kidney injury, have been reported with the use of Beni-kōji CholesteHelp, a functional food containing red yeast rice. Here, we describe 2 cases of kidney injury caused by beni-kōji. The first case had normal kidney function before consuming the product. After several months of use, she developed hypertension. After 6 months of supplement consumption, her estimated glomerular filtration rate (eGFR) dropped to 22.5 mL/min/1.73 m2. A spot urine sample showed a urinary protein-to-creatinine ratio of 2.03 g/g, leading to the diagnosis of Fanconi syndrome. Kidney biopsy showed tubular degeneration. Thirty-five days after discontinuing the supplement, proteinuria resolved and the eGFR returned to baseline level. The second case, who had diabetes and normal kidney function, experienced severe kidney injury (eGFR, 3.5 mL/min/1.73 m2) after 4 months of Beni-kōji CholesteHelp use. He required hemodialysis for >2 weeks but recovered kidney function after the product was discontinued. Kidney biopsy showed tubular injury similar to the first case and glomeruli changes consistent with diabetic nephropathy. These cases indicate that beni-kōji use is associated with tubular toxicity. Further studies are required to identify the precise etiology and mechanism of kidney injury.